2007
DOI: 10.1016/j.expneurol.2007.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction eliminates the aging-related decline in NMDA and AMPA receptor subunits in the rat hippocampus and induces homeostasis

Abstract: Caloric restriction (CR) extends life span and ameliorates the aging-related decline in hippocampal-dependent cognitive function. In the present study, we compared subunit levels of NMDA and AMPA types of the glutamate receptor and quantified total synapses and multiple spine bouton (MSB) synapses in hippocampal CA1 from young (10 months), middle-aged (18 months), and old (29 months) Fischer 344xBrown Norway rats that were ad libitum (AL) fed or caloric restricted (CR) from 4 months of age. Each of these param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 86 publications
14
71
1
Order By: Relevance
“…Finally, the functional enrichments of the genes obtained from the network analysis were characterized by investigating over-represented gene ontology biological processes and pathways Marchal et al 2013), our method was also able to uncover the effect of both interventions on unrecognized molecular processes such as those related to synaptic transmission and glutamatergic signaling. In particular, they suggest the involvement of glutamatergic ionotropic receptors, including AMPA receptor subunits 1, 2 and 3 (GRIA1, 2 and 3), a result reported in connection with CR in rats (Shi et al 2007) and very recently confirmed also in mice (Schafer et al 2015). The involvement of these key signaling molecules for brain functions reinforces the notion that dietary interventions such as those studied herein hold the ability to modulate brain health and function.…”
Section: Enhanced Network-based Analysis: Combining Network and Signsupporting
confidence: 79%
“…Finally, the functional enrichments of the genes obtained from the network analysis were characterized by investigating over-represented gene ontology biological processes and pathways Marchal et al 2013), our method was also able to uncover the effect of both interventions on unrecognized molecular processes such as those related to synaptic transmission and glutamatergic signaling. In particular, they suggest the involvement of glutamatergic ionotropic receptors, including AMPA receptor subunits 1, 2 and 3 (GRIA1, 2 and 3), a result reported in connection with CR in rats (Shi et al 2007) and very recently confirmed also in mice (Schafer et al 2015). The involvement of these key signaling molecules for brain functions reinforces the notion that dietary interventions such as those studied herein hold the ability to modulate brain health and function.…”
Section: Enhanced Network-based Analysis: Combining Network and Signsupporting
confidence: 79%
“…Additional studies, performed in different areas of the rat brain, including some cortical regions, support the hypothesis about the attenuation of some age-induced alterations by CR (Kaur et al 2008;Shi et al 2007). In particular, Shi et al (2007) identified a brain-specific possible mechanism of CR action through the induction of stability or homeostasis of some crucial neural parameters, usually declining with aging. Such CR-induced homeostasis should involve an enhanced defense also against external insults as the age-related, accumulating oxidative stress.…”
Section: Discussionsupporting
confidence: 50%
“…Support for the protective action by CR on mitochondrial functions comes from the data by Sanz et al (2005), showing that CR in brain mitochondria reduces the age-related increased production of ROS at complex I (20 % decrease) by improving the efficiency of mitochondria in avoiding electron leaks at that complex as well as from other studies (Aspnes et al 1997;Barja 2007;Bua et al 2004;Cassano et al 2004Cassano et al , 2006Kang et al 1998;Quintas et al 2012;Stuart et al 2004). Additional studies, performed in different areas of the rat brain, including some cortical regions, support the hypothesis about the attenuation of some age-induced alterations by CR (Kaur et al 2008;Shi et al 2007). In particular, Shi et al (2007) identified a brain-specific possible mechanism of CR action through the induction of stability or homeostasis of some crucial neural parameters, usually declining with aging.…”
Section: Discussionmentioning
confidence: 49%
“…Changes in levels of several different neurotransmitter and/or their receptors have been reported including: decreased levels of acetylcholine and decreased sensitivity of muscarinic receptors to acetylcholine (Lippa et al, 1982;Perry et al, 1993); alterations in levels of NMDA and AMPA glutamate receptors (Shi et al, 2007); and decreased serotonergic input to the hippocampus (Luellen et al, 2007). In addition, neurotrophic support of hippocampal neurons may be diminished during aging as suggested by a decline in the expression of brain-derived neurotrophic factor (BDNF) (Adlard et al, 2005;Luellen et al, 2007) and insulin-like growth factor 1 (IGF-1) (Sonntag et al, 1999).…”
Section: Age-related Cellular and Functional Changes In The Hippocampusmentioning
confidence: 99%